2018
DOI: 10.3390/e20090644
|View full text |Cite
|
Sign up to set email alerts
|

Model Error, Information Barriers, State Estimation and Prediction in Complex Multiscale Systems

Abstract: Complex multiscale systems are ubiquitous in many areas. This research expository article discusses the development and applications of a recent information-theoretic framework as well as novel reduced-order nonlinear modeling strategies for understanding and predicting complex multiscale systems. The topics include the basic mathematical properties and qualitative features of complex multiscale systems, statistical prediction and uncertainty quantification, state estimation or data assimilation, and coping wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 204 publications
(590 reference statements)
1
36
0
Order By: Relevance
“…Understanding and predicting extreme events and their anomalous statistics in complex nonlinear systems are a grand challenge in climate, material, and neuroscience as well as for engineering design. This is a very active contemporary topic in applied mathematics with qualitative and quantitative models ( 1 7 ) and novel numerical algorithms, which overcome the curse of dimensionality for extreme event prediction in large complex systems ( 2 , 8 11 ). The occurrence of Rogue waves as extreme events within different physical settings of deep water ( 12 16 ) and shallow water ( 17 19 ) is an important practical topic.…”
mentioning
confidence: 99%
“…Understanding and predicting extreme events and their anomalous statistics in complex nonlinear systems are a grand challenge in climate, material, and neuroscience as well as for engineering design. This is a very active contemporary topic in applied mathematics with qualitative and quantitative models ( 1 7 ) and novel numerical algorithms, which overcome the curse of dimensionality for extreme event prediction in large complex systems ( 2 , 8 11 ). The occurrence of Rogue waves as extreme events within different physical settings of deep water ( 12 16 ) and shallow water ( 17 19 ) is an important practical topic.…”
mentioning
confidence: 99%
“… described the random variation of atmospheric structure and its physical parameters on various time and space scales. With the improvement of modern nonlinear dynamical [ 50 , 51 ], the atmosphere turbulence in various scale and various space-time plays an important role in saltation and its predictability of atmospheric processes. Therefore, it plays an important role in atmospheric turbulence and related problems.…”
Section: Image Storagementioning
confidence: 99%
“…While these two path-wise measurements are easy to implement and are able to quantify the data assimilation and prediction skill to some extent, they have fundamental limitations. It has been shown in [42,211] that these two measurements fail to quantify the skill of capturing the extreme events and other non-Gaussian features, which lead to misleading results. In fact, concrete examples even in the Gaussian models [42,211] showed that two different predictions can have the same RMSE and PC, but one is way more skillful than the other in capturing the extreme events.…”
Section: Estimating Parameters In the Unresolved Processesmentioning
confidence: 99%